The ontogenesis of Social Representations: A dialectic Perspective - Castorina, Jose Antonio (2010)
The leitmotif of Duveen’s work has been the process through which children assimilate the beliefs of their communities and thus acquire their social identity, which in turn enables them to become social actors. Duveen’s research focused such process in its interconnection with individual activities; his originality as a researcher lies in elucidating this dialectical process. This paper deals with some of Duveen’s works from the perspective of the relation between Social Representations theory and Development Psychology. The article discusses, on one hand, Duveen’s sympathetic and critical view of Piaget’s work; on the other, his interpretation of Vygotsky’s influence on the study of social representations ontogenesis; moreover the paper shows how has Duveen established the conditions for SR to be accepted by developmental psychologists; and finally, there is a review of some of his empirical studies which link psychological development to social identity, as regards the issue of individuation in social psychology.